2019
DOI: 10.3390/en12081573
|View full text |Cite
|
Sign up to set email alerts
|

Oil Factor in Economic Development

Abstract: The research examines the role of oil in the world economy and the evaluation of the oil factor in the economy of Azerbaijan. The error correction model (ECM) has been used in terms of reliability of the obtained results, and assessment has been done by the FMOLS, DOLS and CCR co-integration methods. Engel-Granger and Phillips-Ouliaris co-integration tests have been used for checking the co-integration relations among variables. Times series have been checked whether they are unit root (Augmented Dickey-Fuller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Furthermore, the price of crude oil is used as a benchmark for economic perspectives, currency movement, inflation and to determine the level of political unrest in the Middle East, thus making it one of the most critical global macro indicator [1]. Among the major studies conducted on oil are the impact of oil prices on exchange rate [2][3][4], the impact of oil price shocks on stock market [5][6][7] and also the impact of oil price shocks on other macroeconomic variables mainly GDP [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the price of crude oil is used as a benchmark for economic perspectives, currency movement, inflation and to determine the level of political unrest in the Middle East, thus making it one of the most critical global macro indicator [1]. Among the major studies conducted on oil are the impact of oil prices on exchange rate [2][3][4], the impact of oil price shocks on stock market [5][6][7] and also the impact of oil price shocks on other macroeconomic variables mainly GDP [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Another variable to consider within this factor is the price of energy. Authors such as Humbatova and Qadim-Oglu Hajiyev [5] establish that it is a predominant element in the world economy. In this sense, dependence on fossil fuels, especially oil, still prevails as the main source of supply.…”
Section: Introductionmentioning
confidence: 99%
“…In furtherance to clear the air on the causes of oil price fluctuations, which was generally believed to have outgrown the traditional demand and supply factors, Humbatova and Hajiyev [24] made references, to the Er-Riad summit of 2007 where conclusions where reached on the oil market trend that, it is not related to OPEC decisions. They concluded that the current trend is due to financialisation factors, lack of production capacities in oil production, reduction in the world oil reserves, natural disasters, political events and processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This indicates the exogeneity of oil price which is been determined by many factors that are exogenous to both net importers and exporters of oil, Nigerian inclusive. According to Humbatova and Hajiyev [24] posited that the determinants of oil price range from financial factors, lack of production capacities in oil production, the decline in the world oil reserves, natural disasters, political events and processes, and no one country has the monopoly of determining oil price.…”
Section: Modified Wald Test For Granger Causality Test (M(wald))mentioning
confidence: 99%